Structural analysis of transposition of the main vessels in newborns and infants: combination with other congenital heart defects (Herald of the National Children's Medical Center, 2025)
Background. To study the structures of congenital heart defects operated by us during the newborn and infancy.Materials and methods. The research material included 153 newborns and infants diagnosed with transposition of the great arteries (TGA) who underwent for surgery at the National Children’s Medical Center and private clinics in Tashkent, such as “Ezgu Niyat” and “Ihlos”. The research method was statistical processing performed using Microsoft Excel 2019 software. Indicators of descriptive statistics and variations were determined.Results. Male make up 73.2% of the total number of sick children, while female make up 26.8%. These data confirm the results of various literature sources and studies, which show that the occurrence of TGA is significantly predominant in boys. In 96.08% of cases, TGA is observed in combination with other congenital heart defects. Most cases of TGA are observed in combination with various congenital heart defects. In particular, an PDA occurs in 31.37% of cases, which indicates its significant prevalence among sick children with this pathology. VSD is also a common concomitant defect of the TGA, occurring in 22.88% of cases. In addition, in 20.92% of cases, a combination of both of these congenital heart defects is observed against the background of TGA, which underlines the complexity of the clinical picture in such patients.Conclusion. The obtained data indicate and confirm that in order to better understand the mechanisms of their occurrence and improve diagnostic and treatment methods, it is necessary to further study the interrelationships between various congenital anomalies and TGA. This highlights the need for further research and analysis to better understand all possible combinations and their impact on patient health.
Keywords: congenital malformations; congenital heart defects; transposition of great arteries; structure; patent ductus arteriosus